Análisis comparativo del rendimiento térmico de un captador solar plano para calentamiento de aire con la aplicación de una placa absorbedora interna adicional. - Sailema Moreta, Carlos Patricio (2021)
The proposed research is part of renewable energies, in the development and impact that is taking place on a day-to-day basis, being a technology in constant development, for which the design of a conventional flat collector is varied, creating a double chamber of circulation of air by implementing an additional internal intermediate plate, the system is located in Ecuador, Cotopaxi, Latacunga where the solar radiation indexes are among the highest registered globally. The circulation area is 100cm x 50cm and 10cm, the measurements are made under different environmental parameters, whether high or low looking for a behavior standard, in a measured time of 5 hsp, and with flows given by a blower doing the forced ventilation system, monitoring was given at 20%, 30%, 40% and 50%, which are reflected in the output speed of 2.2m/s, 6.1m/s, 9.1m/s and 11.5m/s respectively. The temperature census variables are arranged at 5 points along the collector to obtain environmental data, air inlet, plate and glass, intermediate points of the collector and the plate, point prior to the air outlet, plate and glass and finally the air outlet, all the data stored locally in an open loop system, on the other hand a meteorological station was located that also obtains the data locally, providing the measurements of irradiation and wind speed, the values to match are 60 data per hour for the analysis and the average performance of 66.03% vs 58.7% for the first case, 69.48% vs 64.58% for the second case, 63.88% vs 53.03% for the third case and 69.33% vs 65.28% for the last case measured with the bias in favor of the proposal in relation to the measured reference.